Awareness of periodontal treatment modalities among dentists of Bathinda district of Punjab: A questionnaire survey - Prabhsimar Kaur; Pooja Arora; Ruby Singla (Wolters Kluwer Medknow Publications, 2023)
Introduction: Periodontal disease is a chronic, inflammatory disease that can lead to various destructive changes in the periodontium as well as systemic health. Periodontology is a fast-growing dental specialty ranging from new advances in diagnosis and treatment. Despite these new advances, the knowledge of periodontal diagnosis and treatment in the minds of general dentists is still lagging. General dentists need to be aware of how to diagnose and treat periodontal disease in the early stage, so there is a need for periodontal health awareness programs to be held at regular intervals. This questionnaire study aims to identify the knowledge regarding periodontal diagnosis and treatment modalities available for patients among practicing dental professionals. Materials and Methods: Two hundred dental practitioners having their dental clinics in any area of Bathinda, Punjab, were interviewed through a questionnaire. Dental practitioners with minimum qualifications of BDS and experience of at least 1 year in the private clinical setup were included in the study. The questionnaire consisted of 15 questions ranging from the chief periodontal complaints of the patients, availability of the treatment, and different techniques used to the level of satisfaction of private dentists after the periodontal treatment. Results: There is enough awareness regarding periodontal problems and its management, as 157 dentists out of 200 refer their patients to periodontists. General dentists perform scaling and root planing, advice oral hygiene instructions, provide diet counseling, and refer to periodontists only for surgical procedure. Lack of maintenance and awareness toward oral hygiene measures was identified by the survey as the chief factor for recurrence of periodontal disease. Conclusion: Such studies performed at different time intervals can provide an idea about the changing trends and patterns of dental treatment performed by general dental practitioners.